Pelvic compensation accompanying spinal malalignment and back pain-related factors in a general population: the Wakayama spine study - Shizumasa Murata; Hiroshi Hashizume; Shunji Tsutsui; Hiroyuki Oka; Masatoshi Teraguchi; Yuyu Ishomoto; Keiji Nagata; Masanari Takami; Hiroshi Iwasaki; Akihito Minamide; Yukihiro Nakagawa; Sakae Tanaka; et al. (Scientific Reports, 2023)
Abstract Some older adults with spinal deformity maintain standing posture via pelvic compensation when their center of gravity moves forward. Therefore, evaluations of global alignment should include both pelvic tilt (PT) and seventh cervical vertebra-sagittal vertical axis (C7-SVA). Here, we evaluate standing postures of older adults using C7-SVA with PT and investigate factors related to postural abnormality. This cross-sectional study used an established population-based cohort in Japan wherein 1121 participants underwent sagittal whole-spine radiography in a standing position and bioelectrical impedance analysis for muscle mass measurements. Presence of low back pain (LBP), visual analog scale (VAS) of LBP, and LBP-related disability (Oswestry Disability Index [ODI]) were evaluated. Based on the PT and C7-SVA, the participants were divided into four groups: normal, compensated, non-compensated, and decompensated. We defined the latter three categories as “malalignment” and examined group characteristics and factors. There were significant differences in ODI%, VAS and prevalence of LBP, and sarcopenia among the four groups, although these were non-significant between non-compensated and decompensated groups on stratified analysis. Moreover, the decompensated group was significantly associated with sarcopenia. Individuals with pelvic compensation are at increased risk for LBP and related disorders even with the C7-SVA maintained within normal range.